Gasification of Solid Recovered Fuels with Variable Fractions of Polymeric Materials † - Alves, Octávio (2022)
Funding Information: This work was funded by FCT–Fundação para a Ciência e a Tecnologia, I.P. (grant no. SFRH/BD/111956/2015), co-financed by Programa Operacional Potencial Humano and União Europeia-Fundo Social Europeu, by the project POCI-01-0145-FEDER-024020 (RDFGAS–Energy recovery of refuse-derived fuel and dehydrated sludge), co-financed by COMPETE 2020–Programa Operacional Competitividade e Internacionalização, Portugal 2020 and União Europeia through FEDER, and also by FCT–Fundação para a Ciência e a Tecnologia, I.P., within the R&D Units Project Scope UIDP/04077/2020 (MEtRICS) and the project UIDB/05064/2020 (VALORIZA—Research Centre for Endogenous Resource Valorization). Publisher Copyright: © 2022 by the authors.